Treatment of Neuronopathic Mucopolysaccharidoses with Blood–Brain Barrier-Crossing Enzymes: Clinical Application of Receptor-Mediated Transcytosis - Hiroyuki Sonoda; Kenichi Takahashi; Kohtaro Minami; Toru Hirato; Tatsuyoshi Yamamoto; Sairei So; Kazunori Tanizawa; Mathias Schmidt; Yuji Sato (Pharmaceutics, 2022)
Enzyme replacement therapy (ERT) has paved the way for treating the somatic symptoms of lysosomal storage diseases (LSDs), but the inability of intravenously administered enzymes to cross the blood–brain barrier (BBB) has left the central nervous system (CNS)-related symptoms of LSDs largely impervious to the therapeutic benefits of ERT, although ERT via intrathecal and intracerebroventricular routes can be used for some neuronopathic LSDs (in particular, mucopolysaccharidoses). However, the considerable practical issues involved make these routes unsuitable for long-term treatment. Efforts have been made to modify enzymes (e.g., by fusing them with antibodies against innate receptors on the cerebrovascular endothelium) so that they can cross the BBB via receptor-mediated transcytosis (RMT) and address neuronopathy in the CNS. This review summarizes the various scientific and technological challenges of applying RMT to the development of safe and effective enzyme therapeutics for neuronopathic mucopolysaccharidoses; it then discusses the translational and methodological issues surrounding preclinical and clinical evaluation to establish RMT-applied ERT.